Expressionism and Women's Roles in Sophie Treadwell's "Machinal" (1928) - Švandová, Denisa (Univerzita Pardubice, 2014)
The primary purpose of this bachelor thesis is to examine the expressionist features and women's roles found in Sophie Treadwell's drama "Machinal." Firstly, the early origins and characteristics of theatrical expressionism are described both in general and in the context of the modern American stage of the early twentieth century. Subsequently, the thesis is focused on the issues of women in the 1920s and the emergence of the New Woman in America. The main part of the thesis is concerned with a detailed analysis of Machinal and explores the expressionist techniques of the play employed to highlight women's roles in all spheres of modern society.
Expresionismus a role žen ve hře "Machinal" (1928) Sophie Treadwell
Keywords: divadelní expresionismus; americký modernismus; role žen; Nová Žena; theatrical expressionism; American modernism; women's roles; New Woman